Pengaruh Model Problem Based Learning Berbasis Wordwall Terhadap Hasil Belajar Kognitif dan Afektif pada Mata Pelajaran PPKn Kelas IV SDN 09 Kepahiang - Putri Utami, Meilan Rafika; Widi Winarni, Endang; Parmadi, Bambang (UNIB Press, 2025)
The aim of this research is to analyze the influence of the modelProblem Based Learning basedwordwall on learning outcomes and the character of cooperation in Civics subjects, analysis and inference. The research design used is researchQuasi-Experimental by designPretest-Posttest Control Group to test the impact of the modelProblem based learning basedwordwall on learning outcomes and cooperative character The type used is quantitative data using non-test instruments in the form of expert validation sheets and tests in the form of learning outcomes tests and Collaboration Character QuestionnairesBased on the research results, it can be concluded that the influence of the modelproblem based learning basedwordwall on Learning Outcomeson the interpretation aspect. Rate-rateposttest in the control class it was (52.50), in the experimental class it was (80.33). Calculation percentageN-Gain amounting to (81%) in the large category. Model UseProblem Based learning basedwordwall on learning outcomes and cooperative character in class IV PPKn learning at SDN 09 Kepahiang has a significant effect on the ability of the Collaborative Character in the analytical aspect. Averageposttest in the control class it was (75.00), in the experimental class it was (80.00). Value percentageN-Gain amounting to (81%) in the large category. Use of modelsproblem based learning basedwordwall has a significant influence on the ability of Cooperation Character, the relationship between the ability of Learning Outcomes and Cooperation Character has a positive relationship with a very strong level of relationship with the coefficient (0.92).